Properties of niobium nitride coatings deposited by cathodic arc physical vapor deposition - Cansever, N. (ELSEVIER SCIENCE SA, 2007)
Thin films of mobium nitride were deposited on high speed steel substrate by cathodic arc physical vapor deposition using -150 V, -200 V and -250 V bias voltages at 1 Pa nitrogen pressure. X-ray diffraction data showed that hexagonal delta-niobium nitride was formed for all bias voltages. Fracture cross-sections revealed the existence of the transition zone structure in all coatings. The maximum hardness was found to be 39 GPa. The Rockwell C adhesion and the scratch test were used to compare adhesion properties. In Rockwell adhesion test the best adhesion was obtained at -150 V bias voltage and in scratch test the cracks were occurred approximately at 3-5 Ns. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: niobium nitride; cathodic arc physical vapor deposition; microstructure; mechanical properties; hardness; adhesion; NBN THIN-FILMS; BEAM-ASSISTED DEPOSITION; MECHANICAL-PROPERTIES; VACUUM; Materials Science; Physics